An experimental and numerical study of wellbore leakage mitigation using pH-triggered polymer gelant. (1st April 2018) - Tavassoli, Shayan; Ho, Jostine Fei; Shafiei, Mohammadreza; Huh, Chun; Bommer, Paul; Bryant, Steven; Balhoff, Matthew T.
Highlights: We introduced a wellbore leakage mitigation method using the pH-triggered polymer gelant. The polymer gelant rheology was sufficiently captured using the Herschel-Bulkley equation. Simulation models were developed for polymer reactive flow with non-Newtonian fluid behavior. Our results show that the pH-triggered polymer gelant can hold up to 70 psi/ft pressure gradient. The application can be used as a remedy for either hydrocarbon fluid or CO2 leakage. Abstract: The potential leakage of hydrocarbon fluids or carbon dioxide from subsurface formations is a primary concern in wellbore integrity, oil and gas production, and CO2 storage. Leaky wells with fractured cement or debonded microannuli are common sources of subsurface fluid leakage. The hydrocarbon fluid or CO2 can migrate through such pathways to shallower formations and ultimately to surface. Cement fractures may have apertures on the order of microns, which are difficult to seal with typical workover techniques. A material that provides low viscosity during the injection but much higher viscosity after injection, with a minimum pressure gradient to yield flow at the target zone, is a potentially effective approach to seal the leakage pathways through cement fractures. pH-triggered polymers are such a material: aqueous solutions with low viscosity at low pH, containing pH-sensitive microgels which viscosify upon neutralization to become highly swollen gels with substantial yield stress that can block fluid flow. For the wellbore leakage application, the large alkalinity of wellbore cement provides the required neutralization. Our coreflood and rheological experiments show that pH-triggered polymer sealants such as polyacrylic acid polymer provide a robust seal if the process is properly designed; however, its long-term applicability depends on the dynamic geochemical environment of the wellbore. The process comprises three stages: (1) injection of a chelating agent as the preflush to ensure a favorable environment for the polymer gel, (2) injection of polymer solution, and (3) shut-in for the polymer gelation. A systematic study was done to understand the conditions under which the polymer gel remains stable and effectively seals the leakage pathways. A numerical model, based on polymer rheological properties and governing mechanisms observed in the laboratory experiments, was developed to simulate the reactive flow and transport of pH-triggered polymers in narrow fractures. Comparison with experiments shows a generally good agreement, despite the relative simplicity of the model. The numerical model was used to investigate further the underlying mechanisms of the process. The results can be used to design effectively the remediation process for a known fracture aperture size of the target zone.